2006
DOI: 10.1002/bjs.5374
|View full text |Cite
|
Sign up to set email alerts
|

Artificial ascites technique for percutaneous radiofrequency ablation of liver cancer adjacent to the gastrointestinal tract

Abstract: Production of artificial ascites can be undertaken safely, making RFA safe and effective for hepatic tumours adjacent to the gastrointestinal tract. In patients with possible postoperative adhesions, confirmation of separation of the liver from surrounding organs is mandatory to avoid thermal injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(103 citation statements)
references
References 21 publications
5
91
1
4
Order By: Relevance
“…Therefore, physiological saline is often injected around the lesion area to improve resolution to visualise this kind of special nodules (Kondo et al, 2008). However, artificial abdominal effusion can help determine the tuberculum close to the gastrointestine (Kondo et al, 2006). Therefore, the proposed methods can strengthen and enhance the adaptation of CEUS.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, physiological saline is often injected around the lesion area to improve resolution to visualise this kind of special nodules (Kondo et al, 2008). However, artificial abdominal effusion can help determine the tuberculum close to the gastrointestine (Kondo et al, 2006). Therefore, the proposed methods can strengthen and enhance the adaptation of CEUS.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent prospective non-randomized study Teratani et al have reported very low incidence of viable tumor (14 out of 2,350 lesions in 1,219 patients, 0.6%), and no difference in local tumor progression rate between nodules in high-risk locations versus those elsewhere [132]. This was attributed to the use of artificial pleural effusion technique, artificial ascites technique [133] and guide-needle method. Table IV shows the clinical studies [21,[97][98][99][101][102][103]105,107,108,[123][124][125][126][127] reporting outcomes after treatment strategies employing RFA for HCC.…”
Section: Radiofrequency Ablation (Rfa) For Hccmentioning
confidence: 98%
“…and most of the solution infused into the peritoneal cavity would disappear in 3 to 7 days in our experience. e. Artificial ascites technique can be used in the cases that hepatocellular carcinoma is located at ventral or dorsal side beneath the liver capsule in order to avoid the thermal effect to the abdominal wall or gastrointestinal tract (Kondo et al, 2006).…”
Section: Learning Of the Knack Of Artificial Ascites Proceduresmentioning
confidence: 99%